Polymorphisms Detection in Heat Shock Brotein70 Gene (HSP70) and its Association with Semen Quality in Local Iraqi Goats - khaleel, Abdulmuttaleb Hazim; Al-Azzawi, Salih Hassan (Diyala Agricultural Sciences Journal, 2022)
Heat shock protein 70 (HSP70) is a vital gene affecting semen quality traits. The study aimed to estimate the breeding values additive dominance variance of Iraqi black goat semen quality and investigate the effect of allele substitution in heat shock protein 70 gene (HSP70) carpine on some semen quality traits (volume, mass motility, a live sperm, and sperm concentration). DNA isolated from 15 Iraqi black goats was subjected to PCR amplification of the caprine HSP70 gene. Used Single-nucleotide polymorphism (SNP) to detect the variant DNA fragments that were sequenced. Synonymous Genotypes were detected on mutation locus (1528C/T). Results showed three genotypes (CC, CT, TT) frequencies of 0.53, 0.40, and 0.07, respectively, and gene frequency of 0.73 and 0.27 C and T, respectively. The population was in Hardy Weinberg equilibrium. The results showed a high level of concentration sperm for CC and CT genotype compared with TT genotype. The CC genotype was associated with negative B.V for volume ejaculate, mass motility, and live sperm percentages and was positively associated with sperm concentration. CT and TT genotypes showed positive B.V for volume ejaculate, mass motility, and live sperm but negative for sperm concentration. CC and TT genotypes showed negative dominance deviation for all traits studied, while heterozygous genotype CT showed positive dominance deviation for all semen quality traits. The highest genetic variation for live sperm (0.816) but most of this variation is from dominance variance (0.653), followed by Genetic variance for mass motility (0.481), most of it from Additive variance (0.39).